2022
DOI: 10.1186/s12912-022-00869-3
|View full text |Cite
|
Sign up to set email alerts
|

The affective component of learning in simulation-based education – facilitators’ strategies to establish psychological safety and accommodate nursing students’ emotions

Abstract: Background Active learning situations such as simulation-based education (SBE) are found to trigger a wide range of emotions among students. Facilitators have an important educational role in SBE which include being attentive and adaptive to students’cognitive and affective responses. Although the importance of emotions in SBE is recognized in facilitator guidelines, little is known about how facilitators accommodate student affect. Hence, this study explores facilitators’ strategies for addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Such learners were afraid of losing their train of thought and feeling stupid and unable to master the task [ 23 ]. Students often report feeling stressed and afraid of making mistakes in situations where others are watching them perform [ 3 , 20 ]. In SBL, it is essential that facilitators create a trusting environment for students, with dynamic interaction and collaboration, to foster a learner-centered perspective [ 34 ] and prevent cognitive overstimulation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Such learners were afraid of losing their train of thought and feeling stupid and unable to master the task [ 23 ]. Students often report feeling stressed and afraid of making mistakes in situations where others are watching them perform [ 3 , 20 ]. In SBL, it is essential that facilitators create a trusting environment for students, with dynamic interaction and collaboration, to foster a learner-centered perspective [ 34 ] and prevent cognitive overstimulation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In SBL, it is essential that facilitators create a trusting environment for students, with dynamic interaction and collaboration, to foster a learner-centered perspective [ 34 ] and prevent cognitive overstimulation [ 21 ]. Previous research has shown that students must feel psychologically safe to achieve their learning outcomes [ 20 , 35 ]. Findings in previous research have shown that students must feel psychologically safe to achieve their learning outcomes [ 20 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations